Religion and American foreign policy, 1945-1960 the soul of containment - Inboden, William 1972- (Cambridge University Press, 2008)
The Cold War was in many ways a religious war. Presidents Truman and Eisenhower and other American leaders believed that human rights and freedom were endowed by God, that God had called the United States to defend liberty, and that Soviet communism was evil because of its atheism and enmity to religion. Along with security and economic concerns, these religious convictions helped determine both how the United States defined the enemy and how it fought the conflict. Meanwhile, American Protestant churches failed to seize the moment. Internal differences over theology and politics, and resistance to cooperation with Catholics and Jews, hindered Protestant leaders domestically and internationally. Frustrated by these internecine disputes, Truman and Eisenhower attempted to construct a new civil religion to mobilize domestic support for Cold War measures, determine the strategic boundaries of containment, unite all religious faiths against communism, and to undermine the authority of communist governments abroad
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Truman, Harry S. / 1884-1972 / Political and social views; Eisenhower, Dwight D. / (Dwight David) / 1890-1969 / Political and social views; Truman, Harry S. / 1884-1972 / Religion; Eisenhower, Dwight D. / (Dwight David) / 1890-1969 / Religion; Evangelische Kirche; Geschichte 1900-2000; Geschichte 1945-1960; Außenpolitik; Geschichte; Cold War; Christianity and politics / United States / Protestant churches / History / 20th century; Religion and politics / United States / History / 20th century; Civil religion / United States / History / 20th century; Religion; USA; United States / Foreign relations / 1945-1953; United States / Foreign relations / 1953-1961